IDENTIFICATION OF TYPES OF INSECT PESTS AND THE LEVEL OF DAMAGE CAUSED TO OIL PALM PLANTS IN AIR MERAH VILLAGE KAMPUNG RAKYAT DISTRICT SOUTH LABUHANBATU REGENCY - Dwi Sapria; Badrul Ainy Dalimunthe; Hilwa Walida; Yusmaidar Sepriani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to identify pest insect species and the level of damage they cause to oil palm plants in Air Merah Village, Kampung Rakyat District, South Labuhanbatu Regency. The research method used is a descriptive quantitative approach with purposive sampling techniques. The results showed that six species of pest insects were found, classified into three orders: Lepidoptera, Coleoptera, and Orthoptera. The most commonly found species was Setothosea asigna. The level of plant damage varied, with an average percentage of 27.46%, categorized as moderate damage. Pest insects attacking oil palm plants have the potential to reduce plant productivity, making it necessary to implement proper pest control strategies to minimize their impact. This research provides essential information for farmers in mitigating pest attacks and improving oil palm production.